The burden of illness in patients with hyponatraemia in Sweden: a population‐based registry study. Issue 4 (20th March 2016) - Gisby, M.; Lundberg, J.; Ländin, M.; O'Reilly, K.; Robinson, P.; Sobocki, P.; Jamookeeah, C.
Summary: Background: Hyponatraemia (HN; serum sodium level < 135 mmol/l) is the most common electrolyte disturbance seen in clinical practice, and is associated with varying spectrum of symptoms. Syndrome of inappropriate antidiuretic hormone secretion (SIADH) is the most common aetiology in hospitalised patients, and can be caused by several different underlying conditions. Aims: The objectives of this study were to retrospectively examine the baseline characteristics, clinical outcomes and hospital resource utilisation of patients with HN and/or SIADH in Sweden over a 10‐year period from 2001 to 2011. Additional analysis was performed on subpopulations of patients with hip fracture, pneumonia and small cell lung cancer (SCLC) to see if trends in outcomes were consistent across a broad range of aetiologies commonly associated with the condition. Methods: Patient information was taken from the Swedish National Patient Registry, the Swedish Cancer Registry, the Swedish Cause of Death Register and the Swedish Prescribed Drug Register. A total of 34, 537 patients (4.38%) were identified with HN and/or SIADH, with the incidence and prevalence rising over the 10‐year study period. Results: Of the 34, 537 patients identified, 841 had hip fracture, 2635 had pneumonia and 106 had SCLC. Compared with matched control patients, those with HN and/or SIADH had a longer length of hospital stay, a higher re‐admission rate and a shorter time to re‐admission. Conclusions: This study showed that HN and/or SIADH negatively impact patient outcomes and healthcare resources related to hospital stay irrespective of the underlying cause. The impact of HN is not confined to the initial hospitalisation, as re‐admission rates are also affected.